Synergistic Antibacterial Effects of Leaf Extracts of Acacia nilotica and Psidium guajava against Extended Spectrum Beta Lactamase (ESBL) Producing E. coli and Klebsiella pneumoniae - Adamu, Salawudeen; Mansur, Abdulrasheed; H. I., Ibrahim; Titus, Inusa; Yusuf Adinoyi, Suleiman; Idris, Nazeef; E.B , Agbo; Tahir, Fatimah (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2024)
The World Health Organization (WHO) recognizes traditional medicine, particularly plant medicine as an important alternative healthcare delivery system for most of the world’s population. The use of plant extracts and phytochemicals both with known antimicrobial properties is of great significance, in the past few years a number of investigations have been conducted worldwide to prove antimicrobial activities from medicinal plants. Hence, the combined antibacterial effects of leaf extracts of A. nilotica and P. guajava against ESBLs-producing E. coli and K. pneumoniae were investigated. Fresh leaves of the plants were collected, processed, and then subjected to three different organic solvents (Methanol, Dichloromethane, and N-Hexane) with varying polarities (high, moderate and low) and water extraction through the maceration method. The various concentrations of the leaf extracts of both plants were subjected to antimicrobial susceptibility testing individually and in combination using agar well diffusion technique. The MIC and MBC were determined according to standard microbiological protocols. The phytochemical analyses revealed the presence of bioactive compounds with exception of anthraquinone and reducing sugars in methanol leaves extracts (ALME+PLME). Methanol extracts of both plants showed highest antibacterial activity against the isolates. The MIC of the plants part was detected at 2.5% and 5% (mg/ml) while the MBC was detected at 5% and 10% (mg/ml). The findings prove that the plants part could be useful in new natural antimicrobial drug development which could serve as potential treatment for the infections caused by the test organisms.